Semantic and pragmatic values of the Italian imperfetto: Towards a common interpretive procedure - Laura Baranzini (Universitat Autònoma de Barcelona, 2015)
This paper proposes an account of the semantics and pragmatics of the Italian indicative imperfect. This tense is described as deriving all of its uses from an extremely reduced core of semantic features as the point of departure to a series of interpretative paths leading to different context-related possible interpretations through a process of pragmatic enrichment. With regard to the temporal parameter, the semantics of the imperfect is described as conveying past temporal reference, with an underdetermined scope. With regard to the aspectual parameter, this tense is defined as not semantically determined at all. Upon pragmatic integration of contextual information, three main classes of meaning effects associated with the imperfect are assumed to emerge: a narrative effect, an evidential effect and an effect of activation of a preliminary phase in relation to the event. Based on the above mentioned features, an overall semantic-pragmatic mapping of the imperfect and of its interpretive procedure is proposed.